2001
DOI: 10.1023/a:1012214807933
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Psychiatric advance directives (PADs) are legal documents that permit competent adults to make choices in the present about their future psychiatric treatment if they lose their decision-making capacity. PADs may provide for the appointment of surrogate decision-makers. The present project was undertaken to obtain opinions from the consumer (the patient), provider, and informal caregiver/surrogate about the Oregon PAD. Results of this pilot study show that the majority of no-PAD group consumers reported that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…The specification of persons to be notified upon hospitalization, preferences for cultural support and methods of escalation in emergencies were items rated most highly across both groups. Similar to other studies in this area (Atkinson et al 2004;Backlar & McFarland 1996;Backlar et al 2001;Swanson et al 2003;2007;Swartz et al 2005;Wilder et al 2012), service users and clinicians varied in opinions when it came to the consideration of coercive measures used in mental health services. Only a third of clinicians, for example, agreed that service users should be able to refuse seclusion via their advance directives.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The specification of persons to be notified upon hospitalization, preferences for cultural support and methods of escalation in emergencies were items rated most highly across both groups. Similar to other studies in this area (Atkinson et al 2004;Backlar & McFarland 1996;Backlar et al 2001;Swanson et al 2003;2007;Swartz et al 2005;Wilder et al 2012), service users and clinicians varied in opinions when it came to the consideration of coercive measures used in mental health services. Only a third of clinicians, for example, agreed that service users should be able to refuse seclusion via their advance directives.…”
Section: Discussionsupporting
confidence: 53%
“…Other studies suggested that advance care planning gave service users an increased perception of empowerment. Henderson et al (2009) reported that service users showed an increase in perceived hope and self-determination upon completing a joint crisis plan and Backlar et al (2001) reported similar findings, whereby service users reported a feeling of empowerment upon completion of a PAD. Both of these studies found, however, that the initial sense of increased empowerment was often followed by less positive feelings, which may be indicative of the powerlessness service users felt in relation to compulsory treatment.…”
Section: Literature Reviewmentioning
confidence: 75%
“…Home treatment team care had the benefit of allowing service users to retain a sense of control and enabling participation in ‘normal’ activities. In contrast to clinicians’ concerns described in the literature [14, 1922], less than half of the service users made a refusal and where there were refusals, valid alternatives were usually presented. Furthermore, while there were some refusals relating to medication and hospitalisation, these treatments were amongst the preferences for some service users, usually at specified stages of relapse.…”
Section: Discussionmentioning
confidence: 96%
“…However, service users have expressed doubts regarding the implementation of their statements [18], and studies suggest that clinicians are concerned that service users will refuse all treatment, or make choices counter to good practice guidelines [14, 1922]. …”
Section: Introductionmentioning
confidence: 99%
“…Arising from the recovery movement, empowerment in mental health services (Anthony, 1993) remains an integral part of the rationale for PADs (Backlar, McFarland, Swanson, & Mahler, 2001). In this context, empowerment is viewed as exerting control over multiple domains of one’s life (Rappaport, 1987).…”
Section: Historical Context Of the Development Of Padsmentioning
confidence: 99%